2020
DOI: 10.1177/1550147720908203
|View full text |Cite
|
Sign up to set email alerts
|

Private vehicle-based crowdshipping for intercity express transportation: Feasibility assessment

Abstract: To support urban sustainable development, cities need innovative green logistics solutions to meet the needs of economic development. Crowdshipping is regarded as a promising sustainable freight solution. This article aims to assess the feasibility of implementing intercity express crowdshipping using private vehicle traveling. The crowdshipping carrier, who drives his or her private vehicle and travels on the intercity route, carries out the express delivery task between the regional cargo center and the disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(63 reference statements)
1
8
0
1
Order By: Relevance
“…Besides, it was found that expectations to pay mass shippers are reasonable and somewhat consistent with the literature on the value of time [39]. Researchers point to a different range of variation in expected courier payment for delivery service from USD 9.2 to USD 19 per hour [7,39].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Besides, it was found that expectations to pay mass shippers are reasonable and somewhat consistent with the literature on the value of time [39]. Researchers point to a different range of variation in expected courier payment for delivery service from USD 9.2 to USD 19 per hour [7,39].…”
Section: Discussionsupporting
confidence: 72%
“…Thus, about 50% of respondents of different gender want to be occasional couriers for a certain amount of money [36]. Couriers were interested in supporting the environment [39], as well as reducing the impact on public transport in the city [42]. The benchmark solutions for crowd shipping help to adjust the business model and market offer of other providers to the needs of different groups of stakeholders [38].…”
Section: Supply Assessmentmentioning
confidence: 99%
“…Moreover, similar conclusions can be also drawn from different approaches that focus on private vehicle-based crowdshipping. For example, Dai et al [52] estimated the environmental and economic benefits that would be brought by crowdshipping in comparison with the traditional delivery, according to participants' stated willingness. Their results are also based on very high adoption rates (~43%) which could achieve a ~68% reduction in CO 2 , ~97% in PM and NO x , but also a ~25% increase in CO.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Some interesting factors like the number of vehicles in a family, work experience in logistics and social media usage were also explored as contributors to the crowd decisions (Ermagun and Stathopoulos, 2018;. Furthermore, Dai et al (2020) and Pourrahmani and Jaller (2021) discovered that attitude towards environmental protection and trust are, respectively, two psychological consideration factors that affect driver-partners' behaviour.…”
Section: Participative Behaviour In Crowd Logisticsmentioning
confidence: 99%